Digital learning's toll: a high prevalence of computer vision syndrome in university students during lockdown - Lim, Co Shin; Ismail, Lili Asma; Othman, Shah Farez; Ithnin, Mohd. Hafidz; Hajar Maidin, Mohamad Hanif (IIUM Press, 2025)
Background: Computer Vision Syndrome (CVS) encompasses a range of ocular and musculoskeletal symptoms, such as dry eyes, eye strain, blurred vision, neck pain, and light sensitivity, resulting from prolonged digital device use. During the COVID-19 lockdown, the shift to online learning increased screen exposure, potentially exacerbating CVS among university students. This study aimed to assess the CVS prevalence, and its associated Internal Symptoms Factors (ISF) and External Symptoms Factors (ESF) among students at UCSI University, Kuala Lumpur, during the pandemic-induced lockdown. Method: A cross-sectional online survey was conducted using the Computer Vision Symptoms Scale 17 (CVSS17) questionnaire. Results: Among 150 participants (mean age 21.36 ± 1.87 years; 99 females, 51 males), the mean CVSS17 score was 34 ± 10.61, with ESF and ISF scores of 24 ± 7.07 and 15 ± 4.95, respectively. A high prevalence of CVS was observed, with 80.67% reporting moderate to severe symptoms. Specifically, 56.67% experienced moderate to severe ESF, while 83.33% reported moderate to high ISF. Female students exhibited significantly higher CVSS17, ESF, and ISF scores compared to males (p<0.01). Conclusion: The findings indicate a substantial prevalence of CVS among students during the lockdown, driven predominantly by internal symptom factors. These results highlight the need for preventive measures to mitigate CVS in digital learning environments.